Development of biocontrol products for postharvest diseases of fruit: The importance of elucidating the mechanisms of action of yeast antagonists. (January 2016) - Spadaro, Davide; Droby, Samir
Abstracts: Background: Impressive progress was made in the last decade in development, registration and commercialization of biocontrol products based on yeast to manage postharvest pathogens of fruit. To successfully inhibit the pathogen infection and development, several possible mechanisms operate in a tritrophic host-pathogen-antagonist interaction system. Scope and Approach: The current reviews focuses on the recent knowledge on the mechanisms by which yeast biocontrol agents (BCAs) interact with pathogens and fruit tissues. The main mechanisms of action explored include antibiosis, mycoparasitism, production of lytic enzymes, induced resistance, competition for limiting nutrients and space, and the role of oxidative stress. Omics techniques can provide a powerful tool to study complex fruit host-pathogen-antagonist-native microflora interactions. Key Findings and Conclusions: Various aspects relevant to mechanisms of action of yeast antagonists have been discussed, including unique environment of surface wounds, iron competition, biofilm formation, cell wall degrading enzymes, and involvement of oxidative stress. Outstanding advancement in molecular and omics technologies revolutionized the research about the physiological status of BCAs and the global effect of the application of BCAs on the transcriptome and/or proteome of fruit. Microbial communities on plant surfaces could impact disease control through their interactions with host plants, pathogens, and BCAs, in a quadritrophic interaction system, hence microbiome research opens new research opportunities. The complex modes of action make antagonistic performance and efficacy more dependent on production, formulation, packing, application, and storage. A deep understanding of the mode of action is essential to develop appropriate formulation and methods of application. Highlights: Many postharvest biocontrol yeast have been developed and commercialized. Yeast can act by competition, antibiosis, parasitism, or host induced resistance. Biofilm formation and quorum sensing can influence the yeast biocontrol efficacy. Oxidative stress plays a key role in the antagonist-pathogen-host interactions. Omics techniques show great potential to study antagonist-pathogen-host interactions.